A systematic review of consumer preference for e-cigarette attributes: Flavor, nicotine strength, and type. - Samane Zare; Mehdi Nemati; Yuqing Zheng (PLoS ONE)
Objective Systematic review of research examining consumer preference for the main electronic cigarette (e-cigarette) attributes namely flavor, nicotine strength, and type. Method A systematic search of peer-reviewed articles resulted in a pool of 12,933 articles. We included only articles that meet all the selection criteria: (1) peer-reviewed, (2) written in English, and (3) addressed consumer preference for one or more of the e-cigarette attributes including flavor, strength, and type. Results 66 articles met the inclusion criteria for this review. Consumers preferred flavored e-cigarettes, and such preference varied with age groups and smoking status. We also found that several flavors were associated with decreased harm perception while tobacco flavor was associated with increased harm perception. In addition, some flavor chemicals and sweeteners used in e-cigarettes could be of toxicological concern. Finally, consumer preference for nicotine strength and types depended on smoking status, e-cigarette use history, and gender. Conclusion Adolescents could consider flavor the most important factor trying e-cigarettes and were more likely to initiate vaping through flavored e-cigarettes. Young adults overall preferred sweet, menthol, and cherry flavors, while non-smokers in particular preferred coffee and menthol flavors. Adults in general also preferred sweet flavors (though smokers like tobacco flavor the most) and disliked flavors that elicit bitterness or harshness. In terms of whether flavored e-cigarettes assisted quitting smoking, we found inconclusive evidence. E-cigarette users likely initiated use with a cigarette like product and transitioned to an advanced system with more features. Non-smokers and inexperienced e-cigarettes users tended to prefer no nicotine or low nicotine e-cigarettes while smokers and experienced e-cigarettes users preferred medium and high nicotine e-cigarettes. Weak evidence exists regarding a positive interaction between menthol flavor and nicotine strength.